MENGANALISIS PEMBELAJARAN IPS DENGAN MEDIA TRADISIONAL DAN MODERN DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 DI SD NEGERI 1 PURBALINGGA LOR - Jiamelatun; Tutuk Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted at SD Negeri 1 Purbalingga Lor with the aim of analyzing Social Studies learning through traditional and modern media in the context of facing the challenges posed by the Fourth Industrial Revolution, employing a case study method with a qualitative approach. The subjects of the research included educators and students from grades IV, V, and VI. Data were collected through interviews, observations, and document analysis. While traditional media such as textbooks and physical objects remain widely utilized, they exhibit limitations in interactivity that may lead to student disengagement. Conversely, modern media, including instructional videos and interactive applications, have proven to be more effective in enhancing understanding and fostering creativity, critical thinking, and collaboration. This research recommends the integration of both traditional and modern media to optimize students' learning experiences and better prepare them to confront increasingly complex global challenges. Additionally, it advocates for the incorporation of diverse teaching methodologies, the provision of technical training for educators, the allocation of technological resources, and the establishment of partnerships with parents. The findings of this study aim to cultivate adaptive and empowered learners in the era of the Fourth Industrial Revolution.